2021
DOI: 10.3390/catal11121548
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Aniline and Chloroanilines Degradation Photocatalyzed by Halloysite-TiO2 and Halloysite-Fe2O3 Nanocomposites

Abstract: The kinetics of photocatalytic degradation of aniline, 2-chloroaniline, and 2,6-dichloroaniline in the presence of halloysite-TiO2 and halloysite-Fe2O3 nanocomposites, halloysite containing naturally dispersed TiO2, Fe2O3, commercial TiO2, P25, and α-Fe2O3 photocatalysts, were investigated with two approaches: the Langmuir–Hinshelwood and first-order equations. Adsorption equilibrium constants and adsorption enthalpies, photodegradation rate constants, and activation energies for photocatalytic degradation wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 38 publications
2
2
0
Order By: Relevance
“…This behavior can be described by means of the Langmuir-Hinshelwood pseudo-first-order kinetic model, which tries to explain that the reactions occur on the surface of the catalyst only if it always has the same adsorption capacity and does not consider the interactions between the absorbed molecules. 37,38 In the case of these two reactions with phenol at 5 and 10 ppm, it agrees with the results presented here, are in agreement with other studies, in which the reactions were governed by first-order kinetics, and the concentration of the contaminant decreases exponentially and, simultaneously, the concentration of the product increases in the same way. To explain the change to zero order in the reactions with phenol at 25 and 50 ppm, it can be suggested that '"zero order reactions appear in heterogeneous systems when the surface of a solid phase is saturated with a reactant, but they are also seen in certain homogeneous systems'.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This behavior can be described by means of the Langmuir-Hinshelwood pseudo-first-order kinetic model, which tries to explain that the reactions occur on the surface of the catalyst only if it always has the same adsorption capacity and does not consider the interactions between the absorbed molecules. 37,38 In the case of these two reactions with phenol at 5 and 10 ppm, it agrees with the results presented here, are in agreement with other studies, in which the reactions were governed by first-order kinetics, and the concentration of the contaminant decreases exponentially and, simultaneously, the concentration of the product increases in the same way. To explain the change to zero order in the reactions with phenol at 25 and 50 ppm, it can be suggested that '"zero order reactions appear in heterogeneous systems when the surface of a solid phase is saturated with a reactant, but they are also seen in certain homogeneous systems'.…”
Section: Discussionsupporting
confidence: 93%
“…S4) showed that, when using concentrations of 25 ppm and 50 ppm, zero order kinetics fit the data, while for lower concentrations (5 and 10 ppm) a first‐order kinetics was more suitable. This behavior can be described by means of the Langmuir‐Hinshelwood pseudo‐first‐order kinetic model, which tries to explain that the reactions occur on the surface of the catalyst only if it always has the same adsorption capacity and does not consider the interactions between the absorbed molecules 37,38 . In the case of these two reactions with phenol at 5 and 10 ppm, it agrees with the results presented here, are in agreement with other studies, in which the reactions were governed by first‐order kinetics, and the concentration of the contaminant decreases exponentially and, simultaneously, the concentration of the product increases in the same way.…”
Section: Discussionsupporting
confidence: 91%
“…The produced radicals can oxidize the aniline in the solution and cause its degradation. [40,41] 4 | CONCLUSION…”
Section: Effect Of Initial Concentration Of Anilinementioning
confidence: 99%
“…In general, the kinetics of heterogeneous catalytic degradation of most organic wastewaters are represented by a pseudo first-order reaction rationalized in terms of the Langmuir-Hinshelwood (L-H) model [64]. In the L-H kinetic model, the rate of degradation takes the following form [65]:…”
Section: Photocatalytic Kineticsmentioning
confidence: 99%